FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI (STUDI PADA SATUAN KERJA PERANGKAT ACEH) - Nadia Mastura; Nadirsyah Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This research are aimed to verify the user involvement, personnel Technical capability, and formalization of information system development toward the performance of the accounting information system in SKPA (Satuan Kerja Perangkat Aceh). The population in this study are all agencies or departements of Aceh goverment offices and secretariat totaled 52 SKPA and was choosen randomly into 35 SKPA. The collecting of data and information needed in this research was done by field research. The data used is primary data collected directly from the subject of research by a questionnaire form. The testing of the influences of independent variables toward dependent variables was done by using multiple regressions model. The results of this research shows that both partially and simultaneously, user involvement, personnel Technical capability, and formalization of information system development are significantly influential to the performance of the accounting information system in SKPA.